Effects of health behaviours on the quality of life of patients following intervention cardiology procedures - Karolina Juraszek; Zdzisława Kalisz; Marcin Wojtkowiak; Magda Kucharczuk; Justyna Kalisz; Stanisław Krajewski (Kazimierz Wielki University, 2019)
Introduction: Diseases of the cardiovascular system are the main health problem of the population not only Polish, but also highly developed countries. Invasive treatment largely contributes to the reduction of mortality, cardiac complications and improves the quality of life of patients. Paying attention to the quality of life of people after cardiac episodes, can help to modify and achieve better therapeutic effects. The aim of a study: Assessment of the impact of health behaviours on the quality of life of patients following intervention cardiology procedures. Material and methods: The study was carried out on a group of 100 people, treated in the Department of Cardiology, the Department of Intensive Cardiac Supervision, the Hemodynamic Work of the Multidisciplinary Hospital of Ludwik Blazek in Inowroclaw. A questionnaire consisting of 22 single-choice questions was used to assess the quality of life of patients. Conclusions: 1. Close to 60% of respondents positively determines their quality of life. 2. The relationship between the effects of pro-health behaviours and quality of life has not been demonstrated. 3. The level of patient awareness of positive health behaviours is small, only a minority progresses according to their principles. 4. Unconsciousness of the health status of patients of the branch causes no reference to staff recommendations. 5. Alarming is prefering anti-health behaviour.